Respuesta del banano a la aplicación de bioestimulantes en el desarrollo y producción - Ávila Pérez, Juan Carlos (2011)
At the farm Venecia, site “El Limon”, located 4 km. near to Machala canton, it was carried out an essay in order to determine the response of banana cultivars to the applying of bio-stimulants for enhance development and production. The following objectives were established: 1. To determine the response to the applying of bio-stimulants for development and production of banana; 2. To achieve an economic analysis on the more effective and cheaper treatment. The treatments in study were: Enerplant, Cytokin, Seaweed extract, Bio-energía, Miller plex 3-3-3, New gibb 10 % compared to a conventional witness, employing the experimental design of blocks at random, with 7 treatments and 4 reapplications, and a total of 28 experimental units. The variables were: height, diameter of pseudo-stem at 0.60 and 1 meter of height, number of leaves per plant at hatching, weeks at harvest, number of cluster per bunch, weight of bunch, grade and length of second and last cluster in bunch, weight of rachis, index of conversion and profitability. The applying of bio-stimulants by injection above the corm enhanced physiologic processes related with height of plant, diameter of pseudo-stem at 0.60 and 1 meter of height, increasing significantly the formation of leaves with Cytokin and Seaweed extract, Enerplant and New gibb as related to Bio-energia and Miller plex and the absolute witness. The most significant effect for the treatments in centered to the increasing of number of clusters per bunch, weight of bunch and the index of conversion, which was determined at 1.18 and 1.20 with Cytokin and Seaweed extract, respectively, followed by Enerplant and New gibb, with an index of 1.13.